2021
DOI: 10.1007/s00784-021-04214-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study showing a lower abundance of Neisseria in the oral microbiome aligns with low birth weight pregnancy outcomes

Abstract: Objectives The objective of this study was to examine the association between the oral microbiome and pregnancy outcomes, specifically healthy or preterm low birth weight (PLBW) in individuals with and without periodontal disease (PD). Material and methods In this prospective clinical trial, we recruited 186 pregnant women, 17 of whom exhibited PD and delivered PLBW infants (PD-PLBW group). Of the remaining women, 155 presented PD and delivered healthy inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
(61 reference statements)
1
9
0
Order By: Relevance
“…The oral microbiome, ranking the second in the microbiomes of the human body, plays a key role in both oral and systemic diseases, such as caries, periodontitis, preterm low birth weight, Alzheimer’s disease, and depression ( Agnello et al, 2017 ; Zhang et al, 2018 ; Deo and Deshmukh, 2019 ; Guo et al, 2021 ; Wingfield et al, 2021 ; Ye et al, 2022 ). As well known, the oral microbiome is in a dynamic balanced state and many factors including the host gene, delivery mode, breastfeeding habits, antibiotics, environment, and physiological changes could influence its composition ( Xu et al, 2015 ; Tamburini et al, 2016 ; Kaan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The oral microbiome, ranking the second in the microbiomes of the human body, plays a key role in both oral and systemic diseases, such as caries, periodontitis, preterm low birth weight, Alzheimer’s disease, and depression ( Agnello et al, 2017 ; Zhang et al, 2018 ; Deo and Deshmukh, 2019 ; Guo et al, 2021 ; Wingfield et al, 2021 ; Ye et al, 2022 ). As well known, the oral microbiome is in a dynamic balanced state and many factors including the host gene, delivery mode, breastfeeding habits, antibiotics, environment, and physiological changes could influence its composition ( Xu et al, 2015 ; Tamburini et al, 2016 ; Kaan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neisseria, which we found to be less common in CWH, has been associated with suppressed salivary levels of IL-6 [42]. Lower abundances of Neisseria in oral samples have been associated with more severe outcomes in influenza and COVID-19 [43,44].…”
Section: Discussionmentioning
confidence: 62%
“…Periodontitis is a chronic, multifactorial inflammatory disease caused by infectious biofilm which could determine, if not properly treated, the destruction of the tooth‐supporting tissues and, finally, tooth loss 1 . During the past few decades, several large‐cohort studies have acknowledged that the various forms of periodontitis may affect over 50% of the population worldwide and also negatively influence several systemic diseases such as cardiovascular disease (CVD), 2,3 preterm birth, 4 metabolic syndrome, 5 and determines an overall low quality of life 6 . Some evidence has shown that the progression of periodontitis can be associated with the dysregulation of some pro‐inflammatory mediators released in the bloodstream, such as metalloproteases, interleukins, prostaglandins, and high‐sensitive c‐reactive proteins (hs‐CRP), 7 which could determine an increased chronic risk of systemic inflammation, endothelial dysfunction, and CVD through a specific oxidative stress pathway 8 …”
Section: Introductionmentioning
confidence: 99%